Transactions of the Medical Society of the State of New York - Munsell, Joel, 1808-1880; Van Benthuysen, C. (Charles), 1817-1881; Grattan, William, 1792?-1827; Prentiss, John Holmes, 1784-1861; Wendell, Cornelius, 1813-1870 (Medical Society of the State of New York, 1809)
"Title of articles published in the Transactions of the Medical society, of the state of New-York, from 1832 to 1857": 1857, p. [183]-228.